Comparative vibrational analysis of thyronine hormones using infrared and Raman spectroscopy and density functional theory calculations - Alvarez, Rosa Maria Susana (2004)
The molecular structures of L-thyroxine (T4), 3,5,3′-triiodo-L- thyronine (T3) and 3,5-diiodo-L-thyronine (T2) were investigated by means of vibrational spectroscopy and density functional theory calculations using the B3LYP hybrid functional and the SDD effective core potential basis set, suitable for heavy atoms. The experimental data were obtained from FT-IR and Raman spectra of the thyroid hormones in the crystalline state. The combined experimental and theoretical approach allows a consistent assignment for most of the fundamental modes in the range between 100 and 1650 cm-1. It was found that, in general, the modes are largely localized in the individual rings and in the linkage connecting both rings. Hence it was possible to identify bands that are dominated by the internal coordinates of the ether bridge and the C-I stretchings. These bands are considered to be sensitive spectral markers for monitoring conformational changes of the hormones after insertion into phospholipid bilayers.